“Asat” Seni Video Instalasi - Heri Nugroho (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2020)
“Asat” is a word taken from Java's Language which mean dry. "ASAT" uses to a title of video's art instalation. This art has duration about 4 minute until 5 minute that presented with looping technic. Above all about this visual art is a well traditional instalation that united with video by projected use video optical projector into a hole well instalation then presenting directly to spectators. So that every spectators that watching this art look into the well hole instalation just like the real well. It is because the visual concept from the video projected into the instalation created a real perspective of the well. Themed about environment's problem which is drought environment's damage cause of human act that wasn't protect their environment with built hotel, mall, apartement, and other large building that damage the environment, made effect to the wells around becoming dry. With visualitation process of drying wells with the sign in the visual video, every spectators is lead to follow the feels of how environment damage process that happened around, also the effect that gained from the damage. The instalation video concept is choosen in order to made this art, aim to create a close relation between spectators and the art. So that real espectation will feels by every socrates, so that will create a deep emotion to the spectators that enjoyed this art. Through this art with all concept so this art has big role in deliver moral message to the spectators to always keep their environment in order to keep long life all creatures on the earth.